Edukasi Teknik Akupresure di Posyandu RW 14 Cibeber untuk Mengurangi Nyeri Punggung pada Kehamilan Trimester III: Edukasi Teknik Akupresure di Posyandu RW 14 Cibeber untuk Mengurangi Nyeri Punggung pada Kehamilan Trimester III - Yanti, Damai; Karwati; Sri Maryati; Santi Susilawati; Rina Saleha; Rinjani Khazanah; Levi Almatia (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
Back pain in third trimester pregnant women is a common complaint that often occurs among pregnant women. As many as 70% of pregnant women in the third trimester experience back pain which causes pregnant women to feel uncomfortable during pregnancy. Pain causes fear and anxiety which can lead to stress and drastic physiological changes during pregnancy. Acupressure is a form of physiotherapy that provides massage and stimulation to certain points on the body which is useful for reducing various aches and pains and reducing anxiety. This Community Service applies the principle of virtuousness, namely that the actions taken pay close attention to the value of caring. This community service activity aims to provide knowledge and skills about pain reduction techniques to overcome complaints of back pain in third trimester pregnant women using acupressure techniques. Participants who took part in this activity were pregnant women in the third trimester who visited posyandu RW 14 Cibeber in January and February 2023. The results obtained were that pregnant women knew complementary ways to reduce back pain in the third trimester so that pregnant women could overcome discomfort in their pregnancy after being given counseling. about acupressure.